Sistem Informasi Penjualan Kerajinan Raga Dayang pada Desa Kutamale Berbasis Web - Br. Karo, Selli Afnita; Perangin-angin, Resianta; Purba, Eviyanti Novita (Universitas Methodist Indonesia, 2024)
Kutamale Village is an area that provides sales facilities for dayang sports crafts located in Kutamale Village. The sales system in Kutamale Village is still carried out manually, namely by visiting Kutamale Village directly. The aim of this research is to make it easier for customers to purchase bodyang handicrafts without having to come directly to Kutamale Village, so in this research a website will be created to make it easier for customers to make purchases online. Programming tools were used to build the Kutamale Village sales website, built using Sublime Open Resources based on HTML, PHP and MySQL database. With a web-based sales system, all transactions can be carried out more easily without being limited by distance or time. This sales information system was provided to Kutamale Village to become a sales promotion media to increase Kutamale Village's income and make it easier to create detailed and detailed sales reports. The research results show that a web-based sales system will make sales transactions and business processes easier.